Estudo teórico da cinética do primeiro estágio de grafitização de um ferro maleável perlítico com o acompanhamento de sua morfologia no microscópio eletrônico de varredura - Silva, Flávio Teixeira da (1970)
The cast irons are ternary alloys of iron, carbon and silicon, that have good mechanical properties. The malleable cast irons are obtained by a heat treatment called "malleabilization", from a white cast iron of a specific composition. The work was based on the theoretical study of the kinetics of first stage graphitization, and on the production of a pearlitic malleable cast iron on which we carried out isothermal treatments for different periods of time, in order to follow the changes of its morfology. These changes were followed using the "Stereoscan" scanning electron microscope at COPPE-UFRJ. The use of deep etching, for the observation of malleablized samples in the "Stereoscan" was studied. The main aim of the work , the confirmation that the "Stereoscan" could be used satisfactorily in the qualitative metallography of malleable cast irons,was achieved.